Development of an e-magazine as a digital learning media for midwifery students - Defera, Wulandari; Yuliva, Yuliva (Indonesian Journal of Health Science, 2026)
The rapid development of digital technology requires innovative learning media that support student centered learning and enhance the quality of midwifery education. This study aimed to develop a digital learning media based on an e-magazine for Essential Midwifery Care in Labour and Newborns and to evaluate its validity, practicality, and student responses. A Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was applied to Diploma III Midwifery students at Poltekkes Kemenkes Padang. Data were collected through interviews, questionnaires, and documentation, and were analysed using descriptive quantitative and qualitative approaches. The e-magazine obtained a validation score of 4.50 from the content expert and 4.40 from the media expert, both categorized as highly feasible. Student responses reached an average score of 4.43, categorized as very good in terms of ease of use, attractiveness, clarity of content, and learning motivation. Survey results indicated that the use of this learning media contributed to enhanced student motivation, engagement, and understanding of essential midwifery care content within a digital learning context. Therefore, the e-magazine is considered appropriate as an innovative learning media in midwifery education. It is recommended that the e-magazine be continuously integrated into learning and that its effectiveness on learning outcomes be further examined.